HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI PETANI DENGAN PERSEPSINYA TERHADAP SEWA LAHAN UNTUK BUDIDAYA TEMBAKAU DI KECAMATAN KEBONARUM KABUPATEN KLATEN - Yetty Susilastuti; Sutarto Sutarto (Universitas Sebelas Maret, 2004)
Tobacco is the one of the plantation comodity which have important role on national economic as.farmer income source an it can increase Gross National Product. To fulfill word market demand, many ways have been done especially to maintenance the tobacco existing. Considering that PT. Perkebunan Nusantara X (Persero) Klaten Tobacco Unit as the one of the plantation company which doesn't have their own land, in the other have they have to keep the company produce, it is necessary to have the land from the another hand by renting. Land rent system is a partnership between farmer land owner with the company as the tenant. On this system, the farmer give their land over to the company and to culturate by the company. The farmer doesn't need to participate on tohacco cultivation. The aim of this research is to study the farmer social economic characteristic, to study the farmer perseption, and to study the farmer social economics characteristic correlation with their perception on land rent for tobacco cultivation at Kebonanan district Klaten Regency. The basic method on this research is descriptive and survey technique. The research location was determined purposively. There are Malangjiwan ang Karangduren village, with the consideration that those two village have much land owner. To determine the amount of the sample farmer in every village. The research use proportional random sampling equation with 40 respondens, simple random sampling was used to determine the sample. Kind and data source consist ofprimary and secondary data. The method to know the farmer social economic characteristic correlation with their perseption on land rent for tobacco cultivation at Kebonarum District Klaten Regency interval equation. The correlation analysis Rank Spearman with SPSS 11,0 for windows program was used to test the farmer social characteristic correlation with their perseption on land rent. The result show that farmer perseption on land rent is quite well fo,mal education, income, the land wide and kosmopolitness high significant on land rent, where as age and non formal education not significant on farmer perseption on land rent for tobacco cultivation at Kebonarum District Klaten Regency.